DETERMINATION OF TOTAL FLAVONOID LEVELS OF ETHANOL EXTRACT MORINGA LEAVES (Moringa oleifera, LamK) BY SPECTROPHOTOMETRY UV-Vis - wilda ayu (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2022)
Moringa (Moringa oleifera L.) is one of the plants that can be used both as food and medicine. The parts of this plant which often used as medicine are the seeds, leaves, and barks. The purpose of this study was to determine the total flavonoid of the ethanol extract of Moringa leaves by UV-Vis spectrophotometry. Extraction method for Moringa leaves using maceration method with 96% ethanol solvent.Furthermore, phytochemical screening was carried out on the ethanolic extract of Moringa leaves using the Thin Layer Chromatography (TLC) method and determination of total flavonoid content by UV-Vis spectrophotometry. The results of the research are Moringa contains alkaloids, flavonoids, tannins, free steroids/terpenoids, and steroids/terpenoid glycosides. Each gram of Moringa (Moringa oleifera, LamK) contain a total flavonoid compound content of 32.261 gQE/g extract with a percentage yield of 5,11%. The conclusion that Moringa leaves contain flavonoids with total flavonoid content of 32.261 μgQE / g extract.